Modeling Determinants of Composite Stock Price Index Based on Multivariable Nonparametric Penalized Spline Regression Model alized Spline - Dhita Hartanti Octavia; Asma Auliarani; Siswanto Siswanto; Anisa Kalondeng (Jurnal Matematika, Statistika dan Komputasi, 2024)
The Composite Stock Price Index (IHSG) is a critical indicator in the Indonesian capital market, playing a central role as one of the key instruments influencing the dynamics of a country's economy. Modeling IHSG can provide a substantial contribution to stakeholders in the capital market, facilitating investment decision-making. Therefore, it is essential to obtain accurate and responsive estimates for IHSG data. The IHSG data used covers the period from January 2020 to December 2022 and tends to be fluctuating. Hence, a spline regression analysis with effective penalized spline estimation is applied to overcome the limitations of assumptions in the relationship between variables. The variables used in the modeling include inflation, exchange rates, interest rates, and IDJ. From the analysis results, optimal values based on the minimum GCV for each variable are sequentially 0.278, 0.904, 0.751, and 0.665. It is also known that these four variables collectively have a 92.1% influence, with inflation having varied impacts, exchange rates exhibiting a stronger negative effect at certain levels, interest rates showing opposite effects depending on their levels, and IDJ having a positive effect on IHSG movements. The significant variability of these impacts indicates that these variables make important contributions. In other words, IHSG fluctuations can be explained by variations in the values of inflation, exchange rates, interest rates, and IDJ.